PENGARUH ELECTRONIC WORD OF MOUTH DAN MEDIA SOSIAL TERHADAP IMPULSE BUYING PADA MAHASISWA FEB UNIVERSITAS TEKNOLOGI SUMBAWA - Arit Juliana; Fendy Maradita (Jurnal Ekonomi dan Bisnis Indonesia, 2023)
Internet has developed rapidly so that it creates many new businesses. Internet changes traditional things into modern, in which internet is not only used as medium of communication but also medium of business, education, government and other activities. Shopping has been considered as important part of everyday life that the purchasing activity might be unplanned (Wu, Chen, & Chiu, 2016). So that all the things committed by the company can be done properly and correctly. The study aimed to examine the effect of Electronic Word of Mouth and Social Media towards Management students of Sumbawa University of Technology. The study used Quantitative method with Associative approach. The technique of data collection used was questionnaire. Total samples of the study were 96 respondents that have been gained through purposive sampling technique. The technique of data analysis deployed was classical assumption testing, multiple regression testing, hypothesis testing and coefficient of determination testing. The result of the study showed that Electronic Word of Mouth and Social Media had Positive and significant effect towards Impulse Buying of Management student of Sumbawa University of Technology. While partially (t test) Electronic Word of Mouth (X1) affected the Impulse Buying of Management student of UTS, Impulse Buying (Y) and Social Media (X2) also affected Impulse Buying of Management Student of Sumbawa University of Technology.